Prevalence of sinonasal disease in children with Juvenile idiopathic arthritis. (14th August 2014) - Pipolo, Carlotta; Turati, Federica; Cressoni, Paolo; Farronato, Giampietro; Angiero, Francesca; Garagiola, Umberto; Di Pasquale, Daniele; Saibene, Alberto M.; Lenzi, Riccardo; Felisati, Giovanni
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis Juvenile idiopathic arthritis (JIA) is the most common chronic rheumatic disease in children and is caused by a multitude of well‐studied disorders. However, the association between JIA and/or its treatment and sinonasal inflammatory disease (SNID) has never been studied. We therefore investigated this relationship to gain more insight into burdening pathologies connected to JIA. Study Design Retrospective evaluation. Methods A retrospective evaluation according to the Lund‐Mackay score of cone‐beam computed tomography scans (CBCT) performed in 70 children affected by JIA and compared to CBCT scans of 124 healthy controls was conducted. The prevalence of sinonasal opacification and adenoid hypertrophy in patients affected with JIA was compared with findings obtained in unaffected children. Results JIA was significantly associated with SNID (P = .030). Of patients with JIA, 18.6% had SNID, whereas in children without JIA, only 8.1% had SNID. The odds ratio values were 5.38 (95% confidence interval [CI]: 1.90‐15.26) for treated and 0.92 (95% CI: 0.18‐4.83) for untreated JIA. No clear difference was found depending on the duration of JIA. No association was found between adenoid hypertrophy and SNID (P = .816). Conclusions Our data suggest that JIA patients, especially when undergoing immunosuppressive therapy, should be subjected to an ear, nose, and throat evaluation. A prospective study including clinical evaluation would be of the utmost importance to provide evidence on which to base comprehensive healthcare for these patients. Level of Evidence 3b. Laryngoscope, 125:291–295, 2015